2004
DOI: 10.1074/jbc.m408038200
|View full text |Cite
|
Sign up to set email alerts
|

A Trimeric Quaternary Structure Is Conserved in Bacterial and Human Glutamate Transporters

Abstract: Neuronal and glial glutamate transporters play a central role in the termination of synaptic transmission and in extracellular glutamate homeostasis in the mammalian central nervous system. They are known to be multimers; however, the number of subunits forming a functional transporter is controversial. We studied the subunit stoichiometry of two distantly related glutamate transporters, the human glial glutamate transporter hEAAT2 and a bacterial glutamate transporter from Escherichia coli, ecgltP. Using blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
81
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 47 publications
20
81
1
Order By: Relevance
“…For example, biochemical studies on human EAAT2 showed that the transporter exists as a trimer (8); cross-linking of pairs of cysteines introduced at the tips of HP1 and HP2 loops, on HP1 tip and TM7, and on HP2 tip and TM7 suggested that these regions are located within close proximity (9,10), in accord with their spatial distances observed in the resolved Glt Ph structure. Additionally, residues in the mammalian EAATs equivalent to the Glt Ph residues Asp-394 and Arg-397, the serine-rich motif (Ser-277-Ser-279), and the conserved NMDGT motif have been proposed to be involved in substrate binding (11)(12)(13)(14), consistent with their interaction with the bound aspartate observed in the high resolution structure of Glt Ph .…”
mentioning
confidence: 51%
“…For example, biochemical studies on human EAAT2 showed that the transporter exists as a trimer (8); cross-linking of pairs of cysteines introduced at the tips of HP1 and HP2 loops, on HP1 tip and TM7, and on HP2 tip and TM7 suggested that these regions are located within close proximity (9,10), in accord with their spatial distances observed in the resolved Glt Ph structure. Additionally, residues in the mammalian EAATs equivalent to the Glt Ph residues Asp-394 and Arg-397, the serine-rich motif (Ser-277-Ser-279), and the conserved NMDGT motif have been proposed to be involved in substrate binding (11)(12)(13)(14), consistent with their interaction with the bound aspartate observed in the high resolution structure of Glt Ph .…”
mentioning
confidence: 51%
“…These data, combined with biochemical evidence, also predict that the functional glutamate transporter has a homotrimeric quaternary structure, which is conserved in bacterial and human transporters (53,156). Glutamate transporters account for the bulk transport of glutamate across the plasma membrane of cells and act quickly to buffer synaptically released glutamate (140).…”
Section: Foran and Trottimentioning
confidence: 95%
“…[ Figure (Haugeto et al, 1996;Yernool et al, 2004;Gendreau et al, 2004). When fresh brain tissue is rapidly homogenized directly in sodium dodecyl sulfate (SDS), only monomers are seen on the Western blots regardless of whether reducing agents have been added (Fig.…”
Section: Sample Quality -Proteolysis and True Oligomers Versus In Vitmentioning
confidence: 99%